Thermal Engineering Volume 1 - Kumar, Shiv.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This highly informative and carefully presented book offers a comprehensive overview of the fundamentals of thermal engineering. The book focuses both on the fundamentals and more complex topics such as the basics of thermodynamics, Zeroth Law of thermodynamics, first law of thermodynamics, application of first law of thermodynamics, second law of thermodynamics, entropy, availability and irreversibility, properties of pure substance, vapor power cycles, introduction to working of IC engines, air-standard cycles, gas turbines and jet propulsion, thermodynamic property relations and combustion. The author has included end-of-chapter problems and worked examples to augment learning and self-testing. This book is a useful reference to undergraduate students in the area of mechanical engineering.
Chapter 1. Basic of Thermodynamics -- Chapter 2. Zeroth Law of Thermodynamics -- Chapter 3. First Law of Thermodynamics -- Chapter 4. Application of First Law of Thermodynamics to Flow Processes -- Chapter 5. Second Law of Thermodynamics -- Chapter 6. Entropy -- Chapter 7. Availability and Irreversibility (Exergy and Anergy) -- Chapter 8. Properties of Pure Substance -- Chapter 9. Vapor Power Cycles -- Chapter 10. Introduction to Working of IC Engines -- Chapter 11. Air-Standard Cycle -- Chapter 12. Gas Turbines and Jet Propulsion -- Chapter 13. Thermodynamic Property Relations -- Chapter 14. Combustion.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Production engineering; Energy storage; Engineering Thermodynamics, Heat and Mass Transfer; Thermal Process Engineering; Mechanical and Thermal Energy Storage